Prognostic value of level IV metastases from head and neck squamous cell carcinoma. Issue 1 (22nd May 2015) - Hoch, Stephan; Katabi, Nour; Daniel, Hanna; Franke, Nora; Wiegand, Susanne; Zimmerman, Annette P.; Mandapathil, Magis; Ferlito, Alfio; Teymoortash, Afshin
Abstract: Background: The purpose of this study was to evaluate the prognostic value of level IV metastases in head and neck squamous cell carcinoma (HNSCC). Methods: The clinical and histopathological data of 111 patients with HNSCC with pN+ neck who underwent a primary tumor resection with unilateral or bilateral neck dissection were analyzed. Results: Level IV metastases were histopathologically proven in 33 patients (29.7%). Pulmonary metastases were observed in 12 of 33 patients (36.4%) with level IV metastases, and in 13 of 78 patients (16.7%) without level IV metastases ( p  = .04). Multivariate analyzes revealed a significant association between level IV metastases and pulmonary metastases ( p  = .038). However, an influence on overall ( p  = .65) or disease‐free survival ( p  = .66) was not observed. Conclusion: Level IV metastases seem to be a predictive factor for pulmonary metastases but not for overall and disease‐free survival in patients with HNSCC. © 2015 Wiley Periodicals, Inc. Head Neck 38: 140–146, 2016